FEW Nexus Approach (water-energy-food nexus) to sustainable development through the UN SDGS - Viana, Hildebrando Mazzardo Marques; Silva, Tania Nunes da (Revista de Administração da UFSM, 2023)
Objective/Purpose: To analyze how the FEW Nexus Approach can contribute to the promotion of sustainable development, having the UN SDGs as a goal and serve as a new epistemological and ontological approach in solving problems related to a complex reality of the present day, such as the sustainable development. Design/methodology/approach: Literature review on the current state of research involving the use of the FEW Nexus Approach, from a global overview to the research scenario on the subject in Brazil. The characterization of the FEW Nexus approach was also made, and its connection with the concepts of sustainable development. Results: It was demonstrated that the FEW Nexus approach, when related to the concept of sustainable development, can seek in the Sustainable Development Goals the tangible goals that, eventually, this paradigm is criticized for not offering. The analysis helps to understand how, from this perspective, FEW Nexus considers the tradeoffs in the management of natural resources, the possibilities for directing public policies and social and economic programs, using the UN SDGs as targets. Originality/Value: Demonstrate the applicability of the FEW Nexus Approach within Applied Social Sciences, where this approach is used much less frequently compared to the Hard Sciences. Possibility of offering a contribution to the elaboration of public policies that can address a crucial problem for sustainability, which is the attack on poverty in Brazil and worldwide.